Implementasi Model Pembelajaran Bisnis Dalam Membangun Karakter Pelajar Pancasila Di School of Universe Bogor - Nanda Ayu Setiawati (Continuous Education: Journal of Science and Research, 2021)
Educational institutions often only produce students who are skilled but do not have an entrepreneurial spirit, so that in the end students are formed as workers who are ready to work, not job creators. The implementation of the ASEAN Economic Community (AEC) which began on December 31, 2015 requires the availability of skilled and highly competent human resources to compete at regional, national and international levels. Education by applying the business learning model in schools is an important component in increasing the competence and independence of participants to seize opportunities in the free market era. Education based on business learning models needs to be done from an early age. The study used a qualitative approach. The data collection techniques used in this study were: interviews, observation and documentation. Data analysis in this study used the interactive model of Miles and Huberman, while the steps taken were data reduction, data modeling, conclusions and verification. The results of this study are recommended to be applied in conventional schools, by collaborating the curriculum and learning models typical of the School of Universe. The business learning model seeks to build students to have the character of Pancasila students who are critical, creative, independent, faithful and devoted and have noble character through entrepreneurial training.